Драконы - Широнина Елена Владимировна (Детская энциклопедия РОСМЭН, 2015)
Экземпляры: ф.8 (20160607) / Инвентарный номер: 56999 / Цена: / Сис.шифр: 82.3(0) / Авт.знак: Ш 64 / ГРНТИ: 17.71.91 / ББК: 82.3(0)я2